Exploring the use of Facebook in the classroom: A Malaysia case study - Lee, Cheng Ean Catherine *; Sangaran Kutty, Vijaya Sooria *; Wong, Shin Pyng * (2015)
With the evolution of social media, including major social networking sites that came into existence in the 21st century, social media has burgeoned into one of the most used channels of communication in the society. As it becomes well recognised for its potential as a social communication channel, recent years have witnessed an increased interest of using social media in higher education. The Social Media Survey 2013 by Pearson shows that 41% of higher education faculty in the U.S. population has use social media in teaching in 2013 compared to 34% of them using it in 2012. The survey results also show the increase use of social media for teaching by educators and faculty professionals because they see the potential in applying and integrating social media technology to their teaching. Many higher education institutions and educators are now finding themselves expected to catch up with the world of social media applications and social media users. This creates a growing phenomenon for the educational use of social media to create, engage, and share existing or newly produced information between lecturers and students and among students. However, the use of social media technologies in higher education is not an easy and straightforward process. Some educators perceived social media tool as an effective educational platform, some perceived that it was not useful at all. Some claimed that it allows them to make the classes more interactive, and some stated that the use of social media can help or hinder the achievement of student learning outcomes. Although there is a growing body of empirical research on the use of social media in higher education in the developed countries, there is not abundance in literature in Malaysia context. This study aims to examine the educational use of Facebook by lecturers and students in a private university in the Klang Valley, Malaysia, and to gauge their attitude towards adopting Facebook in the classroom. The research objectives include 1) investigating the use of Facebook for teaching and learning as well as a communication tool between lecturers and students, and 2) exploring the perception of lecturers and students on the usefulness and ease of use of Facebook in the classroom. Using both qualitative and quantitative research methods, this study will achieve two objectives set and the outcome will provides useful insights for academics interested in using social networking sites for teaching and learning and for researchers interested in pursuing social media in higher education research.